Potential role of endothelial progenitor cells in the pathogenesis and treatment of cerebral aneurysm - Yu, Jin; Du, Qian; Li, Xiang; Wei, Wei; Fan, Yuncun; Zhang, Jianjian; Chen, Jincao (Frontiers in Cellular Neuroscience, 2024)
Cerebral aneurysm (CA) is a significant health concern that results from pathological dilations of blood vessels in the brain and can lead to severe and potentially life-threatening conditions. While the pathogenesis of CA is complex, emerging studies suggest that endothelial progenitor cells (EPCs) play a crucial role. In this paper, we conducted a comprehensive literature review to investigate the potential role of EPCs in the pathogenesis and treatment of CA. Current research indicates that a decreased count and dysfunction of EPCs disrupt the balance between endothelial dysfunction and repair, thus increasing the risk of CA formation. Reversing these EPCs abnormalities may reduce the progression of vascular degeneration after aneurysm induction, indicating EPCs as a promising target for developing new therapeutic strategies to facilitate CA repair. This has motivated researchers to develop novel treatment options, including drug applications, endovascular-combined and tissue engineering therapies. Although preclinical studies have shown promising results, there is still a considerable way to go before clinical translation and eventual benefits for patients. Nonetheless, these findings offer hope for improving the treatment and management of this condition.